MEDIA PEMBELAJARAN BUSUU DALAM PEMBELAJARAN BAHASA ARAB UNTUK PEMULA - Taufik, Taufik; Syifaanddini, Shalihah; Rochmahtika, A'isyah Sabilla; Qiyamullaily, Aliffiyaa Jihan; Nazhifah, Aprilia Imroatun; Azharie, Habib Januar (STIQ Amuntai, 2023)
Learning Arabic as a beginner is a challenge in itself due to differences in accents, grammar, and sentence structure compared to other languages. Moreover, there is the perception that learning Arabic is difficult and tedious. The latest innovations in technology and information in today's era are crucial in the learning process. Mobile technology, especially Android-based media, is expected to address these issues significantly. One Android-based learning application that can be used for learning Arabic as a beginner is Busuu. Busuu is an application developed to assist individuals in learning foreign languages, including Arabic. This research aims to provide contributions and recommendations for developing a more effective and efficient method of learning Arabic using Android-based learning media. The research method used is qualitative descriptive. The research findings indicate that using the Busuu application as an Android-based learning media for beginners is effective and efficient because it is supported by an attractive interface, clear instructions, and valuable features, eliminating the perception that learning Arabic is difficult and tedious.